Laboratory markers predict bone loss in Crohn's disease: relationship to blood mononuclear cell function and nutritional status. - Trebble, T; Wootton, SA; Stroud, M; Mullee, M; Calder, P; Fine, DR; Moniz, C; Arden, N (2004)
BACKGROUND: Crohn's disease is associated with reduced bone density. The power of simple markers of systemic inflammation to identify higher rates of bone loss, in Crohn's disease, is uncertain. This relationship and the role of circulating (peripheral blood) mononuclear cells were investigated in a case-control study. METHODS: Urinary deoxypyridinoline/creatinine and serum osteocalcin concentrations were compared in male and premenopausal females with "active" Crohn's disease (C-reactive protein > or = 10 and/or erythrocyte sedimentation rate > or = 20) (n = 22) and controls with "quiescent" Crohn's disease (C-reactive protein < 10 and erythrocyte sedimentation rate < 20) (n = 21). No patients were receiving corticosteroid therapy. Production of tumour necrosis factor-alpha, interferon-gamma and prostaglandin E(2) by peripheral blood mononuclear cells were measured. RESULTS: Active Crohn's disease was associated with a higher deoxypyridinoline/creatinine (P = 0.02) and deoxypyridinoline/creatinine:osteocalcin ratio (P =0.01) compared with quiescent Crohn's disease, but similar osteocalcin (P = 0.24). These were not explained by vitamin D status, dietary intake or nutritional status. However, production of interferon-gamma by concanavalin A-stimulated peripheral blood mononuclear cells was lower in active Crohn's disease (P = 0.02) and correlated negatively with the deoxypyridinoline/creatinine:osteocalcin ratio (r = -0.40, P = 0.004). CONCLUSION: In Crohn's disease, raised C-reactive protein and erythrocyte sedimentation rate may indicate higher rates of bone loss and, if persistent, the need to assess bone mass even where disease symptoms are mild. This may be partly explained by altered production of interferon-gamma by peripheral blood mononuclear cells.